GENTRIFICATION IN THE MIDDLE CITY OF SOBRAL/CE (BRAZIL - Rodrigues Lopes, Francisco Clébio (Mercator, 2026)
The production of urban space is a profitable business in the modern economy due to the possibility of triggering valorization circuits. Thus, capital needs to induce the creation of differences in space to feed its insatiable hunger for surplus value. Gentrification appears as one of these induced processes because it can stimulate niches of real estate capitalization via expropriation. The medium-sized city of Sobral in the interior of Ceará was the target of a major urban intervention in its historic center to improve its image and attract private investment. The consequences were the rise in land prices, verticalization, and insecurity for residents in adjacent neighborhoods. This article analyzes the urban social transformation in Dom Expedito because it was strongly affected by this complex restructuring of Sobral. It uses the following methodological procedures: bibliographic review, production of statistical data, mapping, and field observation. It is concluded that gentrification has become public policy in urban centers of different demographic sizes, therefore it presents itself as one of the main characteristics of global urbanization.